Security Risks of Climate Change: Case Study of Belgrade - Cvetković, Vladimir M.; Tomašević, Katarina S.; Milašinović, Srđan M. (Sociološki pregled, 2019)
Based on the negative impact of climate change, the aim of quantitative research is to examine models for predicting the impact of demographic and sociocultural factors on citizens’ attitudes to security risks of climate change. Using the random sample method, during the 2019, a survey of citizens was conducted in Belgrade’s central square and included 438 respondents. The results of the research show that the conceived prediction model is statistically significant, and that the attitude of the respondents is influenced by different predictors, the most important of which is the level of education, age and sex of the respondents. Starting from the obtained research results, it is necessary to devise and implement educational programs for improving the awareness of citizens about the negative implications of climate change.